2018
DOI: 10.1007/s00345-018-2475-4
|View full text |Cite
|
Sign up to set email alerts
|

Treating benign ureteroenteric strictures: 27-year experience comparing endourological techniques with open surgical approach

Abstract: In these patients, in terms of patency and patency duration, open surgery was superior to endourology. Nevertheless, endourological treatments offer a safe and less-invasive alternative to delay or avoid open surgery, especially in patients who are unfit for open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Knap et al (31) reported that patients who underwent pelvic radiotherapy before had a higher risk to form a stricture than those without. This evidence has also been enhanced by Son et al (12), who showed that the history of pelvic radiotherapy was significant of stricture recurrence in the multivariable Cox proportional hazards regression analysis. Previously, open repair was recommended for persisting long-term patency rate.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Knap et al (31) reported that patients who underwent pelvic radiotherapy before had a higher risk to form a stricture than those without. This evidence has also been enhanced by Son et al (12), who showed that the history of pelvic radiotherapy was significant of stricture recurrence in the multivariable Cox proportional hazards regression analysis. Previously, open repair was recommended for persisting long-term patency rate.…”
Section: Discussionmentioning
confidence: 74%
“…A total of 18 studies with 697 patients were finally included in this meta-analysis ( 4 , 12 28 ). All studies included were retrospective designed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It postpones or even potentially shuns the needs of open or laparoscopic ureteral reimplantation. [8] Besides, many documents prove that endoscopic interventions are associated with less-invasive and cost-effective. [9]Endoscopic treatments commonly used for ureteral strictures include balloon dilation and endo-ureterectomy.…”
Section: Introductionmentioning
confidence: 99%